1 latte and 8 cupcakes I believe
A----------D----------C
AD = 2x + 6
DC = 4x - 7
the midpoint D splits AC into 2 equal parts....therefore, AD = DC
2x + 6 = 4x - 7
2x - 4x = -7 - 6
-2x = - 13
x = -13/-2
x = 6.5
DC = 4x - 7......4(6.5) - 7 = 19 <===
AD = 2x + 6.....2(6.5) + 6 = 19
42/(-3 * -2)
Multiply the -3 and -2
42/6
Devise
Answer is 7
Answer:
<em>2 solutions</em>
Step-by-step explanation:
Given the expression
2m/2m+3 - 2m/2m-3 = 1
Find the LCM of the expression at the left hand side:
2m(2m-3)-2m(2m+3)/(2m+3)(2m-3) = 1
open the bracket
4m²-6m-4m²-6m/(4m²-9) = 1
Cross multiply
4m²-6m-4m²-6m = 4m² - 9
-12m = 4m² - 9
4m² - 9+12m = 0
4m² +12m-9 = 0
<em>Since the resulting equation is a quadratic equation, it will have 2 solutions since the degree of the equation is 2</em>